Integration of Arduino Uno and IoT Concepts in the Development of Magnetic Field Learning Media: A Qualitative Descriptive Study - Menza Hendri; Dian Pertiwi Rasmi; Novyantri Andika; Syifa Salsabila Wibisana (Postgraduate, University of Mataram, 2025)
Learning about magnetic fields in physics is often challenging because of their abstract nature and difficulty in observing them directly. This study aims to analyze students' perceptions of using an Arduino Uno-based teslameter with a Hall Effect sensor as a technology-based learning medium for magnetic field concepts. This research uses a descriptive qualitative approach with the participation of three 11th grade MIPA students at SMAN 1 Kota Jambi. Data were collected through in-depth interviews validated by physics education experts and analyzed using thematic analysis based on Braun and Clarke's framework. The results of the study indicate that the use of Arduino-based teslameters enhances students' engagement and conceptual understanding of magnetic field phenomena. Additionally, students demonstrated high interest in technology-based learning and provided positive feedback on the development of the device. This study also suggests that integrating the teslameter with a wireless communication module (such as ESP8266) has the potential to connect the device to a cloud system or mobile application, thereby expanding its functionality toward the Internet of Things (IoT). This integration enables real-time and remote observation and measurement of magnetic fields, as well as enhancing the digitalization dimension in 21st-century physics education.